Violation of Women’s Rights: The Kawin Magrib Tradition of the Sasak Muslim Community in Lombok, Indonesia - Sugitanata, Arif; Aminah, Siti; Sunardi, Heru; Sholikhah, Siti Khamidatus (Institut Agama Islam Negeri (IAIN) Pontianak, 2023)
This article investigates violations of women’s rights stemming from the practice of kawin magrib, a form of forced marriage, within the Sasak Muslim community in Lombok, Indonesia. Despite its inherently gender-discriminatory nature, the kawin magrib tradition remains a fundamental aspect of Sasak Muslims’ identity and societal structure. Employing a socio-legal approach and conducting in-depth interviews with nine key informants, this study delves into the persistent reasons behind this tradition and its repercussions on women’s rights. The authors found that the primary objective of kawin magrib is to uphold the moral standards of the younger generation within religious norms. However, the profound adverse effects on women cannot be disregarded. This article highlights the severe psychological trauma endured by women due to this customary law and the potential for men to exploit this tradition deceptively, marrying women without genuine consent. Based on these findings, the article underscores the urgent necessity of reforming this practice, with a strong focus on safeguarding women’s rights and promoting gender equality.